An Islamic-Based Spiritual Program to Improve Workplace Happiness among Inpatient Nurses in Jember, Indonesia - Kholid Rosyidi Muhammad Nur; Nurfika Asmaningrum; Rondhianto Rondhianto; Dicky Endrian Kurniawan; Orachorn Lumprom (Jurnal Keperawatan Soedirman, 2026)
Happiness at work (HAW) plays a critical role in nurses’ performance and their ability to deliver compassionate care, as it affects nurses’ motivation, empathy, and caring behavior. However, culturally grounded interventions to improve nurses’ happiness, particularly within Islamic spiritual frameworks, remain underexplored. Therefore, this study examined the effect of an Islamic-based spiritual program based on local religious and cultural values on nurses’ HAW. This research employed a quasi-experimental design with a non-equivalent control group. The intervention included a structured religious talk on the meaning of life and daily listening to Quranic recitations (murottal) during work for four weeks. The study involved 64 inpatient nurses from hospitals. The participants were assigned to an intervention group (n = 32) and a control group (n = 32). Data were collected using the Shortened HAW questionnaire and analyzed using repeated-measures ANOVA and the Kruskal–Wallis test. The results showed that happiness scores increased significantly in the intervention group (mean difference = 1.53, p < 0.001; η² = 0.354). In contrast, the control group showed minimal change. These findings indicate that Islamic-based spiritual programs can effectively enhance nurses’ happiness at work and may contribute to nurse retention, strengthen caring values, and improve healthcare quality.